Companies of the Agricultural Sector: Economic Rationality and Management (2019)
This article is the result of a research carried out by some associations of small and medium agricultural producers in the southwestern Antioquia region, proposes a reflection on the management in these enterprise organizations of the agricultural sector, linked to the solidarity-based economy. The importance of these partnerships is that they work with the aim of satisfying the needs, aspirations and desires of the individuals, families and communities where are inserted. The methodology used here obeys to the qualitative approach that allows to understand the dynamics in the decision making and relationships that take place among themselves and with other partners the information was obtained through semi-structured interviews that were applied to persons entrusted with the management. The results show that one of the problems of these organizations, is the underdevelopment of the management factor.